The Values of Supervisors in Latvia: the Results from the Pilot Study - Mārtinsone, Kristīne; Ļevina, Jeļena; Mihailovs, Ivans Jānis; Hartmane, Sandra; Upeniece, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
A new profession has been created and is developing in Latvia – a supervisor, and it is important to characterize how its professional basis is created, including the content of the value system. The goal of the pilot study is to characterize the values of the practicing supervisors. This study addresses the following research questions: (a) What are the values of the practicing supervisors? (b) Are there differences between supervisors who practice in different professional fields? and (c) What are the differences of evaluations of importance and attainability of personal values? The participants of this research were 28 supervisors who practice in different professional fields. They filled out an electronic demographic data form online and evaluated the importance and attainability of the offered values on a 5-point Likert scale. The results showed statistically significant differences in the importance of the transcendence value and in the attainability of expediency and practicality value, as well as many differences between the evaluations of importance and attainability of personal values.